Resolución de problemas matemáticos desde la comprensión lectora una gestión necesaria con docentes de educación básica (2021)
Reading comprehension in Latin American basic education doesn't reach the desirable levels, which leads to a negative impact on the resolution of mathematical problems. This research, carried out in two institutions, deals with teacher management in terms of the strategies used with their students in the understanding of texts for the solution of real situations from the resolution of mathematical problems. The compilation of information was carried out in three moments: a documentary review, a semi-structured interview with nine participating teachers and a discussion group, which allowed us to collectively establish the routes of improvement in teaching performance, in order to know and improve pedagogical methods in both institutions, based on the transformation of teaching practices. A route of design and execution of 10 workshops was constructed, oriented to the resolution of problems through the mediation of the teacher, with the participation of teachers, achieving basic transformation of the speech appropriating the reading comprehension and constructing strategies for the improvement of the student performance.